Kuat Tekan Dan Kuat Lentur Beton Gepolimer Fly Ash Bottom Ash (Faba) Hybrid Variasi Extra Water/Faba - Amsal Anwary; Monita Olivia; Iskandar Romey Sitompul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Geopolymers are an alternative cement replacement, made from industrial waste that is rich in silica and alumina, such as fly ash bottom ash. The geopolymerisation bond can beactivated by the activator solution and the curing system at high temperatures. This study utilizes fly ash bottom ash as a geopolymer material and uses an innovative ambient curingease application in the field with additional PCC. This study aims to study the compressive strength and flexural strength of hybrid geopolymer concrete after 28 days of curing with variations of extra water/FABA 0.20 and 0.23. The test results show that the compressivestrength of the extra water/FABA variation of 0.23 has the highest strength value of 15,56 MPa. While the compressive strength of the extra wate /FABA variation of 0.20 has acompressive strength value of 14,62 MPa. The flexural strength value of the extra water/FABA variation of 0,23 has the highest value of 3,08 MPa. While the flexural strength value of the hybrid geopolymer concrete variation of extra water/FABA 0,20 is 2,81 MPa.Keywords : hybrid geopolymer concrete, fly ash bottom ash, PCC, extra water/FABA.